2017
DOI: 10.2147/lra.s141233
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of spinal anesthesia versus general anesthesia for lumbar spinal surgery: a retrospective analysis of 544 patients

Abstract: BackgroundPrevious studies have shown varying results in selected outcomes when directly comparing spinal anesthesia to general in lumbar surgery. Some studies have shown reduced surgical time, postoperative pain, time in the postanesthesia care unit (PACU), incidence of urinary retention, postoperative nausea, and more favorable cost-effectiveness with spinal anesthesia. Despite these results, the current literature has also shown contradictory results in between-group comparisons.Materials and methodsA retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 20 publications
(27 reference statements)
9
35
0
1
Order By: Relevance
“…They observed an increased incidence of hypotension in SA patients, concluding that GA provides greater hemodynamic stability [8]. In the study by Pierce et al, vasopressor use was more frequent with SA [17]. Interestingly, our results show less frequent vasopressor use during SA cases which is consistent with a previous finding [21].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They observed an increased incidence of hypotension in SA patients, concluding that GA provides greater hemodynamic stability [8]. In the study by Pierce et al, vasopressor use was more frequent with SA [17]. Interestingly, our results show less frequent vasopressor use during SA cases which is consistent with a previous finding [21].…”
Section: Discussionsupporting
confidence: 91%
“…Previous publications vary in their hemodynamic findings but provide fewer hemodynamic management details. It is unclear from some reports whether apparent greater stability with SA or with GA reflects specific intervention, thereby confounding interpretation [6, 9, 10, 12, 17]. Our findings about the frequency of vasopressor use are consistent with a previous report [21].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The authors recognize that chloroprocaine is not compared to another anesthetic in terms of effectiveness. However, its non-inferiority to bupivacaine has been previously described in the study by Lacasse et al Current studies also suggest its non-inferiority to general anesthesia and its legitimacy to replace lidocaine [8,22].…”
Section: Study Limitationsmentioning
confidence: 79%
“…For costs of spinal anesthesia and general anesthesia, many studies shown that spinal anesthesia lead to lower health care costs. [2224] Since there was no direct comparison between the costs of these 2 approaches. Thus, more studies were needed to identify the economic costs of the 2 methods.…”
Section: Discussionmentioning
confidence: 99%